2004
DOI: 10.1021/np030370b
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents from Asparagus cochinchinensis

Abstract: Bioassay-directed fractionation of the dried roots of Asparagus cochinchinensis led to the isolation of a new spirostanol saponin, asparacoside (1), two new C-27 spirosteroids, asparacosins A (2) and B (3), a new acetylenic derivative, 3' '-methoxyasparenydiol (4), and a new polyphenol, 3'-hydroxy-4'-methoxy-4'-dehydroxynyasol (6), as well as five known phenolic compounds, asparenydiol (5), nyasol (7), 3' '-methoxynyasol (8), 1,3-bis-di-p-hydroxyphenyl-4-penten-1-one (9), and trans-coniferyl alcohol (10). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 16 publications
0
35
0
1
Order By: Relevance
“…Bioassay-directed fractionation of the dried roots of Asparagus cochinchinensis (Asparagaceae) led to the isolation of some active compounds (130)(131)(132), including a new acetylenic derivative, 3′′-methoxyasparenydiol (92), and asparenydiol (93). These compounds demonstrated moderate cytotoxicities in a panel comprised of KB, Col-2, LNCaP, Lu-1, and human umbilical vein endothelial cells (HUVEC) cells, with IC 50 values ranging from 4 to 20 µg/mL ( Table 9).…”
Section: Acetylenic Metabolites From Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioassay-directed fractionation of the dried roots of Asparagus cochinchinensis (Asparagaceae) led to the isolation of some active compounds (130)(131)(132), including a new acetylenic derivative, 3′′-methoxyasparenydiol (92), and asparenydiol (93). These compounds demonstrated moderate cytotoxicities in a panel comprised of KB, Col-2, LNCaP, Lu-1, and human umbilical vein endothelial cells (HUVEC) cells, with IC 50 values ranging from 4 to 20 µg/mL ( Table 9).…”
Section: Acetylenic Metabolites From Plant Speciesmentioning
confidence: 99%
“…Calicheamicin γ 1 (130), the most prominent member of the calicheamicins, was isolated from Micromonospora echinospora ssp. calichensis and is a remarkable piece of engineering by Nature, which has perfectly constructed the molecule to endow it with its extraordinary chemical and biological properties (196).…”
Section: Bacterial and Cyanobacterial Acetylenic Metabolitesmentioning
confidence: 99%
“…Although no bio-prospecting and isolation work from the Lao PDR has thus far proceeded to the stage of patent filing thereby meriting additional studies (unlike for Vietnam; Zhang et al, 2014Zhang et al, , 2017, through the VietnamLaos ICBG, six medicinal plant taxa from around the country have been evaluated through the compound isolation stage and have been found to contain mostly novel phytochemicals bearing anti-tuberculosis , anti-malarial (He et al, 2005(He et al, , 2006Libman et al, 2008;Ma et al, 2008); and cancer cell cytotoxicity activities (Zhang et al, 2004). With respect to anticancer bio-prospecting from the ICBG field work conducted from 1998 to 2012 in the Lao PDR, at least 34 species yielded 50 extracts with significant activity (IC 50 < 20 μg/ml) in one or more cancer cell lines of a six cell line panel, which notably led to the isolated compounds asparacoside and 3''-methoxy-nyasol (IC 50 > 4 μg/ml, < 10 μg/ml) from Asparagus cochinchinensis (Lour.)…”
Section: Prior Results and Integrative Programing In Laos Andmentioning
confidence: 99%
“…Another subtraction AE9 was also purified via CC using si gel employing 6% methanol:DCM as a mobile phase, which provided compound 3 (87 mg) and 4 (176 mg). Chemical structures (Figure 1) of the isolated compounds 1 (isoagatharesinol; Yang et al, 2004), 2 (gobicusin A), 3 (asparacosin A; Zhang et al, 2004) and 4 (muzanzagenin; Oketch-Rabah et al, 1997) were identified by comparing their Mass and NMR data with reported in literature.…”
Section: Extraction and Isolationmentioning
confidence: 99%